IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA - Ahmad Rifky Ramdhani; Anita Puji Astutik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Independent Learning Curriculum (Kurikulum Merdeka) in developing critical thinking skills among high school students in Islamic Religious Education (PAI) classes. The research employed a library research method following Amir Hamzah’s stages: planning, data collection, source selection and evaluation, and narrative synthesis. Articles were retrieved from Google Scholar and Crossref with inclusion criteria of 2021–2025 publication years, focus on Kurikulum Merdeka at the senior high school/vocational level, and discussion of critical thinking in PAI. Analysis of 16 selected studies indicates that strategies such as Problem-Based Learning (PBL), project-based learning (P5), constructivism, differentiation, self-instruction, and guided inquiry effectively enhance students’ abilities to interpret religious texts, evaluate arguments, and connect Islamic teachings with contemporary issues. Advantages include flexible learning, active participation, and integration of religious values with 21st-century skills, while challenges involve teacher competence, limited project time, and contextual learning resources